THE EFFECTIVENESS OF THE INTEGRATED PREGNANT WOMEN'S CLASS PROGRAM (LASBUDU) AT THE KEMBARAN II COMMUNITY HEALTH CENTER, BANYUMAS REGENCY - Dimas Romadhoni; Taufik Purboyo; Johar Mamuri (Department of Public Administration, University Wijaykusuma Purwokerto, 2026)
This study aims to describe and explain the Effectiveness of the Integrated Pregnant Women's Class Program (LASBUDU) at the Kembaran II Health Center, Banyumas Regency. The research method used is descriptive qualitative research with a case study approach. The determination of informants used the purposive sampling method, and the results of the study used an interactive model. The results of this study indicate that the Integrated Pregnant Women's Class Program (LASBUDU) at the Kembaran II Health Center, Banyumas Regency has several successes and challenges. Although this program is running well, there are still several obstacles such as limited resources. The targets of this program are clear and in accordance with the established criteria. The quality of service for this program is also good and participants are satisfied. However, the achievement of this program has not reached the expected target due to several factors such as the number of pregnant women not meeting the criteria and the lack of support from the media in achieving exclusive breastfeeding.